PENGARUH PENDAPATAN DAN SIKAP KEUANGAN TERHADAP KEPUTUSAN INVESTASI DENGAN PERILAKU KEUANGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Nasabah PT. Amartha Mikro Fintek Point Panarukan) - Nurobikhainih, Mariasri; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Income earned by a person must be managed with a good financial attitude and financial behavior. By optimizing their financial management, customers are able to responsibly plan and realize their future. The purpose of this study was to analyze and examine the effect of income and financial attitudes on investment decisions through financial behavior. The population in this study are customers of PT. Amartha Micro Fintek Point Panarukan.. The sampling technique is determined by probability sampling technique, namely Simple Random Sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that income has a significant positive effect on financial behavior, financial attitudes have a significant positive effect on financial behavior, income has a negative but not significant effect on investment decisions, financial attitudes have a significant positive effect on investment decisions, behavior finance has a positive but not significant effect on investment decisions. The results of the indirect effect hypothesis test show that income has a positive but not significant effect on investment decisions through financial behavior. Financial attitudes have a positive but not significant effect on investment decisions through financial behavior.